The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11243-009-9301-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, DNA interaction and antitumor activities of cobalt(II) and iron(III) complexes of 2-[bis(2-pyridylmethyl)amino] propanic acid

Abstract: Three complexes with 2-[bis(2-pyridylmethyl)-amino] propanic acid (Adpa) were synthesized and characterized. The crystal structure of [(Adpa)CoCl] (1) shows that the cobalt(II) atom is coordinated by three N atoms, one oxygen atom from the Adpa ligand and one chloride, forming a distorted trigonal bipyramidal geometry. The fluorescence titration data indicate the interactions of ct-DNA with complexes [(Adpa)FeCl 2 ] (2) and [(Adpa)-Fe(H 2 O) 2 ] (3) are exothermic, but binding of complex (1) with ct-DNA is end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…The observations also indicated that the 2-PA molecule-in the complex that was the unit of the polymer-might have been attached to Au surface through pyridine-N whereas aminomethyl-N participated in complexation. It is therefore plausible that 2-PA molecule acted as monodentate ligand in this complexation reaction that is different from the reported literature, [10,14,15,18] suggesting the flexidentate nature of the ligand.…”
Section: Chemistryselectcontrasting
confidence: 75%
See 4 more Smart Citations
“…The observations also indicated that the 2-PA molecule-in the complex that was the unit of the polymer-might have been attached to Au surface through pyridine-N whereas aminomethyl-N participated in complexation. It is therefore plausible that 2-PA molecule acted as monodentate ligand in this complexation reaction that is different from the reported literature, [10,14,15,18] suggesting the flexidentate nature of the ligand.…”
Section: Chemistryselectcontrasting
confidence: 75%
“…In summary, literature reports [10,14,15,18] suggest that the reaction between Co(II) and 2‐PA leads to the formation of a chelate complex. However, the current work‐ based on SERRS and mass spectrometric studies‐ revealed that in basic media Co(II) reacted with 2‐PA to produce bridged polynuclear peroxo complex via sigmoidal kinetics, where 2‐PA molecule acted as a monodentate ligand even in the presence of the Au nanoparticles.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations